Inclusive Education through Technology: A Systematic Review of Tools and Practices in Southeast Asia - Aisyah Nurjanah (Worldwide Research Publishing, 2025)
Inclusive education through technology has become a major concern in Southeast Asia, along with efforts to improve access to education for all students, including those with special needs. While technology can offer a wide range of solutions, effective implementation in the region is still limited by a variety of challenges, such as uneven infrastructure and the readiness of educators to utilize digital tools. This article aims to systematically review technology-based inclusive education tools and practices in Southeast Asian countries. The main focus is on the effectiveness of the technological tools used in supporting the diverse needs of students as well as the challenges and opportunities that exist in the region. The study used a systematic review approach, by analyzing 45 related studies published between 2015 and 2023. These studies cover a wide range of technological tools, including educational software, mobile applications, and online learning platforms, applied in the context of inclusive education. The inclusive criteria reviewed included support for students with physical, sensory, and intellectual disabilities. Key findings suggest that while the technological tools used in Southeast Asia have great potential to improve educational accessibility, successful implementation is often hampered by infrastructure issues, teacher unpreparedness, and lack of training. On the other hand, the application of technology in the context of inclusive education also provides opportunities for personalization of learning, which allows for teaching that is more tailored to the needs of diverse students. This article highlights the importance of more structured policies to support the use of technology in inclusive education in Southeast Asia. Improving training for teachers and strengthening digital infrastructure in schools must be top priorities so that technology can provide maximum benefits for all students, especially those with special needs.